The role of strategic analysis (SWOT) in improving Hajj companies’ services: An applied study on Hajj service companies in Makkah - Saqqat, Ahmed Adel (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to highlight the role of strategic analysis (SWOT) in improving the services of pilgrim service companies. The study was applied to pilgrim service companies based on previous studies that addressed the subject. The descriptive analytical approach was used to identify the elements of strength and weakness, opportunities and threats, and then identify the survival and continuity of the company. The study reached several results, the most important of which are: The use of strategic analysis contributed to knowing the strategy adopted by In Hajj service companies.
Keywords: Strategic analysis; strengths; weaknesses; opportunities; threats